'Grey zones' in the differential diagnosis of lymphoma pathology. Issue 6 (June 2019) - Kim, Wook Youn; Pugh, Matthew; Dojcinov, Stefan; Quintanilla-Martinez, Leticia
Abstract: The 2016 World Health Organization classification of lymphoid malignancies has further improved basis for pathological diagnosis and better characterization of lymphoproliferative conditions. It includes a range of new entities and expanded requirements for molecular analysis, but reliance on close integration of the clinical, pathological and molecular features still remains the cornerstone for diagnosis. Despite the advances in knowledge and refined diagnostic criteria, certain areas of lymphoma pathology remain difficult and contentious. We provide a review of some entities which continue to represent diagnostic "grey zones", with potentially overlapping pathological, molecular or clinical features, but in most instances require specific treatments to achieve best clinical outcomes. We focus on: clarifying diagnostic ambiguity between nodular lymphocyte predominant Hodgkin lymphoma and T-cell/histiocyte rich B-cell lymphoma, including the relevant differential diagnoses; key features and differential diagnosis of mediastinal grey zone lymphoma; characteristics of high grade B-cell lymphomas, with particular reference to their genetic features as defining diagnostic parameters; pathological overlaps of EBV-positive lymphoproliferations and their differential diagnosis with EBV-positive classic Hodgkin lymphoma.